Media dalam Membentuk Kultur Agama Masyarakat - Anton Widodo (Communicative : Jurnal Dakwah dan Komunikasi, 2021)
The discussion on the relation of Islamic symbols and the analysis of religious multiculturality in people's lives is a theme that is often highlighted. Even more attention will be paid when a description of this is presented along with the presence of the mass media in carrying out their activities. The media as part of the study is very impressive to study its participation in the analysis of Islamic symbols and forming religious multiculturality in society. The existence of the media to fulfill daily life definitely gives a different direction to the way of thinking that will be carried out by the community itself. The media is still used as an inseparable material with the existence of communication in the world of Islamic symbols. Therefore, communication can be used as the most important basis in fulfilling the discussion of Islamic symbols in people's daily lives. This fact is also balanced with the growth of mass media that is happening at this time in accommodating every dynamic of the growth of the world of da'wah. The media also has many impacts on people's lives, but it must be able to make the existence of communication media as an interest that cannot be separated from the people, because mass media is a very powerful form of communication media used at this time to introduce any information to the public. we have. With a note that the information we convey is useful information for many people. The media that exist today are a very effective choice for disseminating information quickly and precisely considering the rapid era of globalization today. The very influential role of the mass media is one of the causes of the importance of the media as a marker of character and behavior as well as people's experiences. That's why so many people try to use mass media as a means of propaganda for the ideals, ideas, values ​​and norms that the people themselves want to create. It depends on what kind of mass media manager itself can be wise when implementing the role of mass media in real terms. Then viewed from the side of the condition of the Indonesian people, which consists of many tribes and cultures as well as other diversity, the media must be able to manage this diversity into something that is valuable to the nation and is also the strength of the nation itself.